Experimental study of dropwise condensation on plasma-ion implanted stainless steel tubes - Kananeh, Ali Bani; Rausch, Michael Heinrich; Fröba, Andreas Paul; Leipertz, Alfred (International Journal of Heat and Mass Transfer, 2006)
Plasma-ion implantation was used to achieve stable dropwise condensation of saturated steam on stainless steel tubes. For the investigation of the efficiency of plasma-ion implantation regarding the condensation process a condenser was constructed in order to measure the heat flux density 4 and the heat transfer coefficient h, for the condensation of steam on the outside surface of a single horizontal tube. For tubes implanted with a nitrogen ion dose of 10(16) cm(-2), the heat transfer coefficient h(c) was found to be larger, by a factor of 3.2, in comparison to values theoretically calculated by the corrected Nusselt film theory. The heat flux density 4 and the heat transfer coefficient h, were found to increase with increasing ion dose and steam pressure. The heat transfer coefficient decreases with increasing surface subcooling as it has been found in former work for dropwise condensation on ion implanted vertical plates. (c) 2006 Elsevier Ltd. All rights reserved.
Keywords: dropwise condensation; heat transfer coefficient; plasma-ion implantation; stainless steel tubes; surface free energy